2018
DOI: 10.1016/j.arth.2017.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Is Associated With Short-Term Complications Following Total Hip Arthroplasty

Abstract: COPD patients are more likely to suffer from postoperative complications following THA when compared to non-COPD patients. Many of these complications are medical, pulmonary evaluation and medical optimization are a critical step in preoperative management for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
4
16
1
Order By: Relevance
“…Various authors have suggested the importance of the discharge dispostion in patients admitted due to other causes such as COPD or some specific interventions. 39–41 However, with respect to patients with CAP, only Dong et al and the present study have found an association between the discharge dispostion and readmission. Other variables related to the quality of care were studied to assess these aspects but no association with readmission was found.…”
Section: Discussioncontrasting
confidence: 73%
“…Various authors have suggested the importance of the discharge dispostion in patients admitted due to other causes such as COPD or some specific interventions. 39–41 However, with respect to patients with CAP, only Dong et al and the present study have found an association between the discharge dispostion and readmission. Other variables related to the quality of care were studied to assess these aspects but no association with readmission was found.…”
Section: Discussioncontrasting
confidence: 73%
“…Interestingly, we noted that COPD patients had a shorter operative time as compared to the non-COPD group. A similar finding has been reported in a previous study investigating the impact of COPD on postoperative outcomes in total hip arthroplasty (THA) (12). A plausible reason given by the authors in that study was that surgical and anesthesia teams would attempt to finish cases faster in order to prevent the occurrence of postoperative complications in patients with an already higher baseline co-morbidity burden.…”
Section: Discussionsupporting
confidence: 82%
“…10 COPD is an important independent medical risk factor of re-intubation for both noncardiac and cardiac surgery. [11][12][13] In an NSQIP study of approximately 450,000 subjects, the unadjusted rate of re-intubation was 5.5% among those with COPD. 14 A 2-fold increase in the odds of 30-d re-intubation was observed in subjects with a bleeding disorder compared to those without.…”
Section: Discussionmentioning
confidence: 99%